War production in caves, 1942 (1942)
1942 1939-1945 "War production in caves, 1942" [HFR0185], 1942 Four schemes for underground factories, strongly supported by the Minister of Aircraft Production, Lord Beaverbrook, were approved between 1940-1942. The first scheme housed 8000 aircraft equipment workers in an unfinished Underground railway tunnel and the second used an existing cavern in the Midlands for Browning gun production. The third scheme involved digging a tunnel near Coventry to house engineering plants dispersed after the heavy bombing raids. The final scheme provided over 2 million square feet of factory space in underground quarries for aircraft engine manufacture. The last scheme proved very expensive [£12 million at 1944 prices] and the programme was discontinued. This drawing comes from The Illustrated News, 25 July 1942.